High-voltage switchgear and controlgear. Classification of indoor enclosed switchgear and controlgear for rated voltages above 1 kV up to and including 52 kV related to the use in special service conditions with respect to condensation and pollution Part 304, (14th June 2019) - British Standards Institution,
No abstract available